Question #cf6c6

1 Answer
Sep 6, 2017

Answer:

See a solution process below:

Explanation:

Equation 1: Solve for two points which solve the first equation and plot these points:

First Point:

For #x = 0#

#y = 0 - 2#
#y = -2# or #(0, -2)#

Second Point:

For #x = 2#

#y = 2 - 2#
#y = 0# or #(2, 0)#

We can plot the two points on the coordinate plane and draw a line through them to graph the line:

graph{(y-x+2)(x^2+(y+2)^2-0.03)((x-2)^2+y^2-0.03)=0 [-15, 15, -7.5, 7.5]}

Equation 2: Solve for two points which solve the second equation and plot these points:

First Point:

For #x = 0#

#y = (-2 * 0) + 7#
#y = 0 + 7#
#y = 7# or #(0, 7)#

Second Point:

For #x = 2#

#y = (-2 * 2) + 7#
#y = -4 + 7#
#y = 3# or #(2, 3)#

We can plot the two points on the coordinate plane and draw a line through them to graph the line:

graph{(y+2x-7)(x^2+(y-7)^2-0.05)((x-2)^2+(y-3)^2-0.05)(y-x+2)(x^2+(y+2)^2-0.05)((x-2)^2+y^2-0.05)=0 [-15, 15, -7.5, 7.5]}

Solution:

We can see from the graph, the lines cross at #(3. 1)#:

graph{((x-3)^2+(y-1)^2-0.05)(y+2x-7)(y-x+2)=0 [-10, 10, -2.5, 7.5]}